SKALA CYBERSLACKING PADA MAHASISWA - Simanjuntak, Ermida; Fajrianthi, Fajrianthi; Purwono, Urip (Faculty of Psychology, Diponegoro University, 2019)
Cyberslacking in the educational context is defined as using internet in the classrooms for non-academic purpose during lectures. One of student cyberslacking scale was developed by Akbulut, Dursun, DÃ¶nmez, & Sahin through researches towards Turkey undergraduate students. This scale consists of items to measure non-academic internet access activities during lectures. Those activities are sharing, shopping, real time updating, accessing online content and gaming/ gambling. This study aims to adopt the Cyberslacking Scale of Akbulut dkk. in the context of undergraduate Indonesian students. Subjects for adopting this scale are 46 male and 156 female undergraduate university students (N=202) with age range between 18-23 years. Second order confirmatory factor analysis (CFA) was conducted to analyze this scale. The results showed that dimension of sharing, shopping, real time updating, accesing online content, and gaming/gambling dimension are positively represented cyberslacking construct. Thus the cyberslacking scale can be used in Indonesian educational context.